Consumer Contract Governance in a Deregulating Japan - Taylor, Veronica (Victoria University of Wellington Law Review, 1997)
This article analyses patterns of governance - how public and private policy networks are managed - in consumer contracts in a deregulating Japan. It outlines the structure of Japan’s service industry and consumer problems, before considering the framework for a juridical intervention, bureaucratic regulation and pressures for further legislative activity. As the question of how to curb excesses of power in a deregulated environment governed by multiple agents become more acute, consumer governance seems likely to change, and with it the utility of current theories of how law operates in Japan.